2022
DOI: 10.1021/acs.langmuir.2c02849
|View full text |Cite
|
Sign up to set email alerts
|

Lipidated Lysine and Fatty Acids Assemble into Protocellular Membranes to Assist Regioselective Peptide Formation: Correlation to the Natural Selection of Lysine over Nonproteinogenic Lower Analogues

Abstract: The self-assembly of prebiotically plausible amphiphiles (fatty acids) to form a bilayer membrane for compartmentalization is an important factor during protocellular evolution. Such fatty acid-based membranes assemble at relatively high concentrations, and they lack robust stability. We have demonstrated that a mixture of lipidated lysine (cationic) and prebiotic fatty acids (decanoic acid, anionic) can form protocellular membranes (amino acid-based membranes) at low concentrations via electrostatic, hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(33 citation statements)
references
References 59 publications
2
31
0
Order By: Relevance
“…The critical vesicle concentrations (CVCs) of the TTAC–TPP and TTAC–PPi systems were measured by pyrene I 1 / I 3 and merocyanine 540 assays. 55,60 The CVC of TTAC–TPP (∼0.75 mM) was lower than the CVC of TTAC–PPi (∼1.25 mM) (Fig. S23 and S24, ESI†).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The critical vesicle concentrations (CVCs) of the TTAC–TPP and TTAC–PPi systems were measured by pyrene I 1 / I 3 and merocyanine 540 assays. 55,60 The CVC of TTAC–TPP (∼0.75 mM) was lower than the CVC of TTAC–PPi (∼1.25 mM) (Fig. S23 and S24, ESI†).…”
Section: Resultsmentioning
confidence: 97%
“…It was reported that the NR maxima in vesicles are around 624 nm while in micelles they are around 640 nm. 54,55 These experiments suggest that TPP and PPi assist in the formation of vesicular structures. Apart from the emission maxima, the emission intensity was also monitored.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[16][17][18] Model amphiphiles such as fatty acids, 19,20 cyclophospholipids, 21 and amino-acid-based amphiphiles might have played important roles during protocell formation. [22][23][24][25][26] Protocell membrane assembly could provide a unique environment, that may be considered a "reaction territory" to support primitive catalytic reactions. The self-assembly of the amphiphiles and the formation of protocellular membranes could have supported primitive organocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…The self-assembly of the amphiphiles and the formation of protocellular membranes could have supported primitive organocatalysis. 22,27,28 Since amino acids and small peptides were proposed as prominent ancient organocatalysts, 3 we hypothesize that amino acid-based primitive amphiphiles might have supported membrane-surfaceassisted catalytic reactions. Therefore, it is interesting to establish the prebiotic synthesis of amino acid-based amphiphiles, their catalytic efficacy, and substrate selectivity, if any!…”
Section: Introductionmentioning
confidence: 99%